Human Rights Protection in the Islamic Family Law: A Case Study Concerning Domestic Violences - Putra, Dedisyah; Acela, Nuriza (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Islam and life are inseparable because Islam elevates the dignity of women and restores their rights, which had been violated by male dominance, religious traditions, and group fanaticism prior to the advent of Islam, when women’s rights were disregarded. This study employs qualitative methods by accumulating and analyzing library data descriptively and analytically. This article aims to describe the concept that Islam comes with a mission to restore the rights of women who have been marginalized as a result of prolonged jahiliyah conditions. This paper examines the relationship between Islam and human rights in the context of domestic violence, using family law and women's rights terminology. On the other hand, this review will focus on family law in the context of human rights preservation and domestic violence prevention